Evaluación psicológica del trastorno depresivo: estudio de caso - Mora Vásquez, Carolina Esperanza (My University, 2021)
The present investigative work aims to analyze the presence of depressive disorder through personological psychodiagnosis, based on the bibliographic search and the methodology of the historical-cultural approach, with such an approach it is intended to carry out the analysis of the personality through the experiences of the subject and The categories that comprise it, among them are mentioned: the system of motives, resilience, attachments, learned hopelessness, self-efficacy, coherence and locus of control. A man with symptoms of depression participated in the study, and since childhood he has had problems in social and emotional development. This research corresponds to a qualitative approach, in addition a narrative-biographical design is used that provides essential information on the historical and experiential path of the subject, in turn a descriptive-interpretive scope is used that allows analyzing and interpreting the important details of the narrative. Instruments such as the Hamilton Scale were applied, which is aimed at detecting depressive symptoms and the Beck Inventory, aimed at identifying anxiety, both items maintain a high level of reliability, which favors the diagnosis. The results obtained allow us to recognize that the subject presents a moderate Depression, as well as the results of Anxiety at a moderate level; regarding the narration of the experiences of the subject, it is possible to determine that there is a prevalence of depressive symptoms and an inadequate development is identified in the different areas of the individual.
El presente trabajo de investigación tiene como objetivo analizar la presencia del trastorno depresivo mediante el psicodiagnóstico personológico, tomando como base la búsqueda bibliográfica y la metodología del enfoque histórico-cultural, con tal enfoque se pretende realizar el análisis de la personalidad mediante las vivencias del sujeto adulto y las categorías que la integran, entre ellas se mencionan algunas: el sistema de motivos, la resiliencia, los apegos, la desesperanza aprendida, la autoeficacia, la coherencia y el locus de control. En el estudio realizado participó un hombre adulto con síntomas de depresión, y que desde su niñez ha tenido problemas en el desarrollo social y afectivo emocional. Esta investigación corresponde a un enfoque cualitativo, además se utiliza un diseño narrativo-biográfico que proporciona información indispensable del recorrido histórico y vivencial del sujeto, a su vez se utiliza un alcance descriptivo-interpretativo que permite analizar e interpretar los detalles importantes de la narrativa. Se realizó la aplicación de los instrumentos como la Escala de Hamilton, que está direccionado a la detección de síntomas depresivos y el Inventario de Beck, encaminado a identificar la ansiedad, ambos reactivos mantienen un nivel de confiabilidad elevado lo que favorece para el diagnóstico. Los resultados obtenidos permiten reconocer que el sujeto presenta una Depresión moderada, al igual que los resultados de Ansiedad en un nivel moderado; en cuanto a la narración de las vivencias del sujeto se logra determinar que existe la prevalencia de los síntomas depresivos y se identifica un desarrollo inadecuado en las diferentes áreas del individuo.
Keywords: DEPRESION; ANSIEDAD; VIVENCIA; PERSONALIDAD